Locomotive Assignment Optimization Including Train Delays - Kasalica, Sandra; Mandić, Dragomir; Vukadinović, Vojislav (Promet - Traffic&Transportation, 2013)
Intention– Cyclic locomotive assignment planning is a specific type of organization of locomotive usage, and in fact, it means putting the complete workload to a closed chain, which is repeated periodically. The concept of cyclic locomotive assignment planning type organization in the area of train traction has proven in practice as the best one, but as it is made for in-advance defined timetable and without considering the stochastic nature of the timetable realization process, it leads to incompatibility in using locomotives. Methodology – Methodology defined in this paper contains: research of train delays on the Serbian Railways and Montenegrin Railways networks, analysis of the real system organization of locomotive usage in conditions of train delays, theoretical thesis of solving the problem of optimal cyclic locomotive assignment planning in conditions of train delays, designing of a model with algorithms, preparing the software package, testing the model and program with results, as well as the conclusions drawn from the complete research project. Results– The optimization model of cyclic locomotive assignment planning during the process of making timetable including train delays has been defined. Conclusion –The obtained results have shown as expected, that the larger delays of trains required a larger number of locomotives. However, by using this model it is possible to optimize the required number of locomotives, taking into account the real time delays of trains.